SAFE STREETS FOR REAL PEOPLE: A CASE STUDY OF NEOCONSERVATIVE POLICY FROM A STRUCTURAL SOCIAL WORK PERSPECTIVE - LeBlanc, Élyse (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2021)
The Safe Streets Act of Ontario [SSA] ostensibly regulates aggressive panhandling, but is widely regarded as a contemporary vagrancy law that criminalizes people experiencing homelessness. This paper presents a case study of the SSA in which an ideological analysis is employed to highlight the extent to which dominant political paradigms shape conceptions of social problems and their appropriate remedies. Specifically, it explores the mechanisms inherent to neoconservative ideology which serve to blame individuals for their problems and construct vulnerable people in need of support as villains worthy of exclusion and punishment, rationalizing punitive responses to poverty. This approach is diametrically opposed to the aims of structural social work and therefore must be challenged. An alternative policy response is presented as it might emerge from a social democratic worldview, which is more congruent with social work ideals. This paper thus illustrates how radically the nature of social problems is transformed when viewed through contrasting ideological lenses. The paper concludes that there is great value in using political paradigms to unpack existing and create new policy in the context of structural social work mandates; doing so contributes to the paradigm shift that a profession committed to fundamental social change must help ignite.